The Effect of Islamic Education Learning Activities and Student Learning Motivation on Student Character at MTs Negeri 2 Jatisari Karawang - Saepudin; Dedeh Kurniasih; Susilawati; Irena Laras; Muhamad Hanifah (QuranicEdu: Journal of Islamic Education, 2026)
This study examines the effects of Islamic Religious Education (IRE/PAI) learning activities and students’ learning motivation on students’ character at MTs Negeri 2 Jatisari, Karawang. A quantitative approach with a correlational survey design was employed. The population comprised 777 students, and a 15% proportional sample yielded 117 respondents. Data were collected using Likert-scale questionnaires (15 items each) measuring PAI learning activities (X?), learning motivation (X?), and students’ character (Y). Reliability testing indicated adequate internal consistency (? X?=0.762; ? X?=0.850; ? Y=0.811). Multiple linear regression was conducted after meeting classical assumptions (Tolerance=0.962; VIF=1.039; Durbin–Watson=2.037). The findings show that PAI learning activities and learning motivation jointly have a significant effect on students’ character (F(2,114)=3.426; p=0.036; R²=0.057). Partially, PAI learning activities do not significantly predict students’ character (B=0.072; p=0.455), whereas learning motivation has a significant positive effect (B=0.183; p=0.022). These results suggest that character development in the madrasa context is more sensitive to students’ motivational factors. Therefore, improving PAI instruction should prioritize meaningful learning experiences, consistent value habituation, and need-supportive classroom practices to strengthen character outcomes.